The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0047-20852007000200007
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine and bupropion have no in vitro effects on lynphocyte proliferation and viability

Abstract: Palavras-chaves

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…There is also a greater probability of finding changes in lymphocyte 5HT transporters in patients with severe depression, melancholy and associated clinical co morbidities 1,2 . Furthermore, another study reported for the fist time that bubropion has no effect on lymphocyte proliferation 15 and, in the present study, cells pre-treated with bupropion maintained NK activity. Previous studies observed a tendency for improvement of the immune response with the administration of other double action antidepressants, with at least some serotonin action (mirtazapin) 9 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…There is also a greater probability of finding changes in lymphocyte 5HT transporters in patients with severe depression, melancholy and associated clinical co morbidities 1,2 . Furthermore, another study reported for the fist time that bubropion has no effect on lymphocyte proliferation 15 and, in the present study, cells pre-treated with bupropion maintained NK activity. Previous studies observed a tendency for improvement of the immune response with the administration of other double action antidepressants, with at least some serotonin action (mirtazapin) 9 .…”
Section: Discussionsupporting
confidence: 61%
“…In order to contribute to answer this question we decided to evaluate separately the effect in the IS of a drug with only serotonergic activity (paroxetine) and a drug with only noradrenergic/dopaminergic activity (bupropion) 13 . As we had the results regarding the activity of both drugs on lymphocyte proliferation 15 we decided to examine their citotoxicity and NKA action.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study conducted by Ronchetti et al . (2007)[27] in bupropion and paroxetin, no significant differences in cell viability were found. The major objective of our study was to find whether WB is capable of producing genotoxic or cytotoxic effects in human peripheral lymphocytes.…”
Section: Discussionmentioning
confidence: 99%